Purification and Properties of Amine Oxidase from Epicotyls of Pisum sativum - McGowan, Roy E. (1971)
A procedure has been developed for the purification of amine oxidase (E.C. 1.4.3.4) from etiolated pea epicotyls (Pisum sativum cv. Little Marvel). The enzyme is sensitive to copper chelating reagents and carbonyl reagents, but is not inhibited by sulfhydryl reagents. The purified enzyme has a molecular weight of 1.85 × 10(5), as determined by sedimentation equilibrium centrifugation, and has been shown to be specifically stimulated by phosphate.